The art of cardboard : big ideas for creativity, collaboration, storytelling, and reuse - Zimmer, Lori (Rockport Publishers, 2015)
The Art of Cardboard showcases the grand and imaginative scale of cardboard art and design. Inside, you'll find...cardboard creations from around the world! You'll discover the process of each art form, as well as tricks of the trade, from small clever projects to huge art installations...Lori Zimmer guides you through...large-scale art production, immersive environments, working from intuition, collaboration, the artist's role in society, alternative creative economies, contemporary mythology, storytelling and more.